An immunosensor based on a high performance dual-gate oxide semiconductor thin-film transistor for rapid detection of SARS-CoV-2. Issue 5 (22nd February 2022) - Kim, Jingyu; Jeong, Sehun; Sarawut, Siracosit; Kim, Haneul; Son, Seong Uk; Lee, Seungheon; Rabbani, Gulam; Kwon, Hyunhwa; Lim, Eun-Kyung; Ahn, Saeyoung Nate; Park, Sang-Hee Ko
Abstract : We present an immunosensor based on a dual-gate oxide semiconductor thin-film transistor as a platform for detecting SARS-CoV-2. Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the agent of an infectious disease that has led the WHO to declare its highest level (6) pandemic. The coronavirus disease 2019 (COVID-19) has spread rapidly around the world, and the number of confirmed cases has passed 246 million as of November 2021. Therefore, precise and fast virus detection protocols need to be developed to cope with the rapid spread of the virus. Here, we present a high performance dual-gate oxide semiconductor thin-film transistor (TFT)-based immunosensor for detecting SARS-CoV-2. The immunosensor has an indium tin oxide sensing membrane to which the antibody against the SARS-CoV-2 spike S1 protein can be immobilized through functionalization. The dual-gate TFT was stable under ambient conditions with near-zero hysteresis; capacitive coupling yields a 10.14 ± 0.14-fold amplification of the surface charge potential on the sensing membrane and improves the pH sensitivity to 770.1 ± 37.74 mV pH −1 above the Nernst limit. The immunosensor could rapidly detect the SARS-CoV-2 spike S1 protein and cultured SARS-CoV-2 in 0.01× PBS with high antigen selectivity and sensitivity. Our immunosensor can accurately measure the electrical changes originated from SARS-CoV-2, without the need for polymerase chain reaction tests or labeling.